Konflik Hukum Agraria Terhadap Pembangunan Jalan Tol Di Sumatera Barat (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
This research in-depth investigates agrarian law conflicts that arise in connection with toll road construction in the West Sumatra Province. The main focus of this research is on exploring the position of Minangkabau community customary land in the context of inheritance law. An in-depth analysis was carried out on the role of the 1945 Constitution of the Republic of Indonesia and Law Number 5 of 1960 concerning Basic Agrarian Principles (UUPA) in regulating the revocation of rights to customary land for the public interest. This research also explores comparisons with other regions in Indonesia to reveal variations in legal approaches in dealing with similar conflicts. Thus, this research aims to understand the complexity of conflicts that arise along with these infrastructure projects. The results of this research provide an illustration that the agrarian law conflict in West Sumatra is not only limited to the revocation of rights to customary land, but also involves aspects of inheritance law which significantly influence the position of the Minangkabau people. The implications of these findings will be explained comprehensively to provide in-depth insight into the dynamics of agrarian law conflicts in the context of infrastructure development in Indonesia.